Chest wall abscess with intestinal perforation and distal catheter migration of Ventriculoperitoneal (VP) shunt without anal extrusion: A case report - Farhad Bal'afif; Donny Wisnu Wardhana; Tommy Nazwar Alfandy; Lulik Inggarwati; Ryan Ardiansyah; Ferry Ferdiansyah; Mustofa Mustofa (Elsevier, 2022)
Hydrocephalus is the symptomatic accumulation of cerebrospinal fluid (CSF) within the brain ventricles. Common treatments include direct etiological procedure e.g. a Ventriculoperitoneal (VP) shunt, which can potentially lead to complications such as infection, obstruction, cerebrospinal fluid pseudocyst, bowel perforation, shunt catheter migration, peritoneal inclusion cyst, and spontaneous VP shunt catheter extrusion. A rare case of extrusion on a 2 years old boy was reported; the individual in question came with a lump on his chest and was diagnosed with hydrocephalus on the patent right VP shunt. From a theoretical perspective, treatment of extrusion can be done via emergency removal, antibiotic treatment, nil per oral, and reinsertion if needed. From the particular case, it was concluded that treatment is possible with removal of the catheter and reinsertion of the VP shunt and through postoperative monitoring.